2022
DOI: 10.1111/jfpe.14091
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of food processing equipment

Abstract: Conventional unit operation practices followed in food processing value chains would cause the post-harvest spoilage due to their low capacity, high processing cost, and labor intensive. In this context, the food engineers have been developing special-purpose equipments and tools to reduce the human drudgery, energy consumption and to increase the production capacity of the food processing plants. Currently, researchers have developed the post-harvest processing equipments for cereals, pulses, horticultural pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The waxes, pollutants, lignin, pectin, and hemicellulose constituents of the 5 wt% alkali‐treated TMCF (Figure 2) have been entirely or evenly removed, giving the impression that it becomes rough. Exchanging the tension loading among them improves the adhesive ability and enhances the filler's characteristics, which promotes the filler to matrix adhesion 90–92 . Madivoli et al 93 reported the analogous morphology after the TEMPO modification of the Oryza sativa cellulosic nanofibers.…”
Section: Resultsmentioning
confidence: 99%
“…The waxes, pollutants, lignin, pectin, and hemicellulose constituents of the 5 wt% alkali‐treated TMCF (Figure 2) have been entirely or evenly removed, giving the impression that it becomes rough. Exchanging the tension loading among them improves the adhesive ability and enhances the filler's characteristics, which promotes the filler to matrix adhesion 90–92 . Madivoli et al 93 reported the analogous morphology after the TEMPO modification of the Oryza sativa cellulosic nanofibers.…”
Section: Resultsmentioning
confidence: 99%
“…Through analysis and pre‐test, the significant range of influence of each factor on the evaluation index is determined, and the level of test factors is shown in Table 1; Using the orthogonal test method of three factors and three levels (Pandiselvam & Kothakota, 2022), 50 walnuts in each group were selected for the test, the results are shown in Table 2. and the optimal working parameters and structural parameters of the shell breaking test device were obtained.…”
Section: Bench Test Of Shell Breaking Mechanismmentioning
confidence: 99%